2017
DOI: 10.1111/cpr.12393
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits the chemotherapy‐induced repopulation by suppressing the arachidonic acid metabolic pathway and phosphorylation of FAK in ovarian cancer

Abstract: Our observation suggested that Berberine could inhibit the chemotherapy-induced repopulation of ovarian cancer cells by suppressing the AA pathway and phosphorylation of FAK. And these findings implicated a novel combined use of Berberine and chemotherapeutics, which might prevent ovarian cancer recurrence by abrogating early tumour repopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 35 publications
(83 reference statements)
1
39
0
Order By: Relevance
“…Previous studies demonstrated that berberine possesses various pharmacological activities and may treat different diseases, such as sepsis, inflammation, diabetes and cancer, by multiple mechanisms, e.g., halting cell cycle progression and triggering apoptosis (Chen et al, 2017;Hou et al, 2017;Zou et al, 2017). In cancer cells, berberine could induce apoptosis and inhibit the chemotherapyinduced repopulation by suppressing the arachidonic acid metabolic pathway Zhao et al, 2017), enhance chemosensitivity through dose-orchestrated AMPK signaling , and reverses hypoxia-induced chemoresistance through the inhibition of AMPK-HIF-1a , In addition, berberine also plays a role in the regulation of immune response, oxidant stress, tissue fibrosis, and autophagy with low side effects and good resistance, suggesting its clinical and research values (Yang et al, 2019). In this study, berberine alone or in combination with doxorubicin maintained the N1 neutrophil phenotype to prevent carcinogenesis and chemotherapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that berberine possesses various pharmacological activities and may treat different diseases, such as sepsis, inflammation, diabetes and cancer, by multiple mechanisms, e.g., halting cell cycle progression and triggering apoptosis (Chen et al, 2017;Hou et al, 2017;Zou et al, 2017). In cancer cells, berberine could induce apoptosis and inhibit the chemotherapyinduced repopulation by suppressing the arachidonic acid metabolic pathway Zhao et al, 2017), enhance chemosensitivity through dose-orchestrated AMPK signaling , and reverses hypoxia-induced chemoresistance through the inhibition of AMPK-HIF-1a , In addition, berberine also plays a role in the regulation of immune response, oxidant stress, tissue fibrosis, and autophagy with low side effects and good resistance, suggesting its clinical and research values (Yang et al, 2019). In this study, berberine alone or in combination with doxorubicin maintained the N1 neutrophil phenotype to prevent carcinogenesis and chemotherapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is the most lethal gynecological malignancy and the fifth leading cause of cancer-associated deathin women (1,2). Ovarian cancers are responsible for more than half of the female genital tract cancers caused deaths, with more than 2 million new cases being diagnosed every year (1,3,4). Despite significant advances in surgery and chemotherapy, the long-term survival rate of patients with ovarian cancers is still very low (3).…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (BBR) is an isoquinoline alkaloid extracted from the rhizomes of Coptis, which displays multiple biochemical functions and anti‐microbial and anti‐inflammatory activities . BBR also exhibits anti‐cancer activities through suppressing cell proliferation and inducing tumour cell apoptosis . BBR reportedly directly binds with DNA, radio‐sensitizes lung and oesophageal cancer cells and sensitizes ovarian cancer cells to cisplatin and PARP inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 BBR also exhibits anti-cancer activities through suppressing cell proliferation and inducing tumour cell apoptosis. [16][17][18][19][20][21][22] BBR reportedly directly binds with DNA, radio-sensitizes lung and oesophageal cancer cells and sensitizes ovarian cancer cells to cisplatin and PARP inhibitors. 23,24 Consequently, BBR may interfere with cellular DNA repair and would be a promising adjuvant agent to sensitize breast cancer cells to chemotherapeutic drugs.…”
mentioning
confidence: 99%